Pertussis seroprevalence in adults, post-partum women and umbilical cord blood - Fallo, Aurelia (2014)
Pertussis is a vaccine-preventable disease that affects people of all ages. Young adults who have lost their immunity to pertussis are the major source of infection in infants. Given the steady increase of pertussis cases, new prevention strategies are required. Objective. To assess pertussis seroprevalence in adult blood donors, post-partum women, and umbilical cords. Metod. Measurement of total titers of anti-Bordetella spp. (Bordetella) antibodies using an enzyme-linked immunosorbent assay. Serum samples from 103 donors, 101 post-partum women and 100 umbilical cords were analyzed. Titers ≤80 were considered of low impact against the disease. The assessment included transplacental transfer of antibodies and the umbilical cord/maternal ratio of antibody titers. Results. Donors mean age was: 28 ± 6 years old. Median anti-Bordetella titers: 320; interquartile range (IQR):160-320; 10% had titers ≤80. Post-partum women mean age was: 26 ± 6 years old. Median anti-Bordetella titers:160 (IQR:80-320), with titers significantly lower than in female donors (p= 0.00002). Titers ≤80 were found in 30% of post-partum women. Median anti-Bordetella titers in umbilical cords: 160 (IQR: 80-160). Titers ≤80 were more frequently found in umbilical cords than in mothers (44% versus 30%, p= 0.04). Transplacental transfer was 0.83. Umbilical cord titers were equal to maternal titers in 54% of cases, lower in 37%, and higher only in 8%. Conclusion. Titers of anti-Bordetella antibodies in post-partum women were significantly lower than in female blood donors. Titers ≤80 were found in 30% of post-partum women and 44% of umbilical cords. These data may account for the high rates of pertussis in young infants who have not yet completed their vaccination schedule.